Azitromicin efficacy as associated therapy for chronic periodontitis treatment - Chumpitaz-Cerrate, Victor (2014)
The aim of this research was to compare systemic administration of azitromicin associated to root scaling and planning to the use of chlorhexidine mouth rinses associated to scaling and root planning, and scaling and root planning only for reducing probing depth and clinical attachment in adult patients with diagnosed of chronic periodontitis. For the trial 42 individuals with chronic periodontitis were selected, they were randomly distributed in three groups as follows: group A associated therapy of azitromicin with root scaling and planning; group B associated therapy with chlorhexidine and root scaling and planning; and group C root scaling and planning only. Probing depth and clinical attachment were recorded before treatment and every month for the next 6 months. The results showed better reduction in probing depth (before treatment: 5.70 ± 0.42 mm; during treatment: 1st month: 2.20 ± 0.36 mm, 2nd month: 2.14 ± 0.33 mm, 3rd month: 2.09 ± 0.32 mm, 4th month: 2.04 ± 0.29 mm, 5th month: 1.96 ± 0.27mm, 6 th month: 1.93 ± 0.25mm) and better clinical attachment in group A compared to group B and C. It was shown that systemic administration of azitromicin associated to root scaling and planning resulted in better outcomes compared to the other two treatments, when used for chronic periodontitis.